2014
DOI: 10.1016/j.celrep.2013.12.004
|View full text |Cite
|
Sign up to set email alerts
|

Loss of MEC-17 Leads to Microtubule Instability and Axonal Degeneration

Abstract: SUMMARY Axonal degeneration arises as a consequence of neuronal injury and is a common hallmark of a number of neurodegenerative diseases. However, the genetic causes and the cellular mechanisms that trigger this process are still largely unknown. Based on forward genetic screening in C. elegans, we have identified the α-tubulin acetyltransferase gene mec-17 as causing spontaneous, adult-onset, and progressive axonal degeneration. Loss of MEC-17 leads to microtubule instability, a reduction in mitochondrial nu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

9
118
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 86 publications
(127 citation statements)
references
References 58 publications
9
118
0
Order By: Relevance
“…Interestingly, αTAT1 (also known as MEC‐17) is a specific acyltransferase that promotes α‐tubulin acetylation on lysine 40 (K40), and many studies have verified that elevated levels of acetylated α‐tubulin are a marker of stable microtubules 35, 36. Furthermore, this study also revealed that the loss of MEC‐17 (αTAT1) expression leads to microtubule instability, axonal degeneration, and disrupted axonal transport in Caenorhabditis elegans 37. In addition, MEC‐17 (αTAT1) deficiency leads to reduced α‐tubulin acetylation and impaired migration of cortical neurons in mice 38.…”
Section: Discussionmentioning
confidence: 61%
“…Interestingly, αTAT1 (also known as MEC‐17) is a specific acyltransferase that promotes α‐tubulin acetylation on lysine 40 (K40), and many studies have verified that elevated levels of acetylated α‐tubulin are a marker of stable microtubules 35, 36. Furthermore, this study also revealed that the loss of MEC‐17 (αTAT1) expression leads to microtubule instability, axonal degeneration, and disrupted axonal transport in Caenorhabditis elegans 37. In addition, MEC‐17 (αTAT1) deficiency leads to reduced α‐tubulin acetylation and impaired migration of cortical neurons in mice 38.…”
Section: Discussionmentioning
confidence: 61%
“…Indeed, mouse and zebrafish models of CMT2A have provided crucial information on the importance of Mfn2 in normal physiology and disease (Detmer et al, 2008;Vettori et al, 2011;Chapman et al, 2013;Bannerman et al, 2016). Moreover, recent studies in small model organisms such as the fruit fly Drosophila melanogaster and the nematode Caenorhabditis elegans have been instrumental in characterizing the role of mitochondria in neuronal health (Neumann & Hilliard, 2014;Rawson et al, 2014;Babic et al, 2015;Neumann et al, 2015;Melkov et al, 2016;Morsci et al, 2016;Yu et al, 2016). However, despite this progress, several outstanding questions and major goals for future research remain and are outlined below.…”
Section: Outstanding Questions and Future Directionsmentioning
confidence: 99%
“…The main disadvantage of EMS-density mapping is lower mapping resolution owing to the lower density of EMSinduced SNPs and the inability to use allele frequencies across the chromosome for refining the mapping region. EMS-density mapping has successfully been used to clone numerous mutants (Zuryn et al 2010(Zuryn et al , 2014Svensk et al 2013;Neumann and Hilliard 2014;Steciuk et al 2014;Tocchini et al 2014;Rauthan et al 2015).…”
Section: Advantages/disadvantages (Ems-density Mapping)mentioning
confidence: 99%